IgG4 Autoantibodies Attenuate Systemic Lupus Erythematosus Progression by Suppressing Complement Consumption and Inflammatory Cytokine Production - Pan, Qingjun; Xiao, Haiyan; Shi, Lei; He, Yiming; Cai, Jun; Wu, Jing; Li, Aifen; Ye, Lin; Yang, Chen; Liu, Hua-feng (Frontiers in Immunology, 2020)
Pathogenic autoantibodies can cause inflammation and tissue injury in systemic lupus erythematosus (SLE). Although IgG4 is considered noninflammatory owing to the unique structure of its hinge region, the role of IgG4 autoantibodies in SLE remains largely unknown. The titers of serum anti-nuclear-IgG antibodies (ANA-IgG) and anti-nuclear-IgG4 antibodies (ANA-IgG4) in newly-diagnosed SLE patients were detected. The effects of IgG4 purified from SLE patients (SLE IgG4) and healthy controls on complement consumption and inflammatory cytokine production were evaluated in vitro. The therapeutic effects of mouse IgG1 (functionally resembles human IgG4) purified from lupus-prone MRL-lpr/lpr mice (lupus IgG1) and control mice on disease progression were examined in MRL-lpr/lpr mice. The results showed that SLE patients with equal titers of total serum ANA-IgG (1:3,200) were divided into group Ⅰ with lower ANA-IgG4 titers (≤ 1:10) and group Ⅱ with higher ANA-IgG4 titers (≥ 1:100), and disease activity, inflammatory cytokine production, complement consumption, and renal-function parameters in group Ⅰ SLE patients were more severe than those in group Ⅱ. Further, compared with control IgG4, SLE IgG4 inhibited complement consumption by autoantibody-autoantigen immune complexes, and also inhibited inflammatory cytokines production by SLE PBMCs in vitro. Moreover, compared with control IgG1, lupus IgG1 exhibited a therapeutic effect on lupus by attenuating disease progression in MRL-lpr/lpr mice. These finding, for the first time, suggest that IgG4 autoantibodies can attenuate SLE progression by suppressing complement consumption and inflammatory cytokine production. Hence, this study may provide novel therapeutic strategies against SLE and other autoimmune diseases.